NIKAH SIRI DALAM PERSPEKTIF ISLAM - Sobari, Ahmad (JURNAL ILMU SYARIAH, 2013)
Nikah Siri is a term developed in the community, which means marriage under the hand; a process of marriage in accordance with the rules and regulations in Islam, as their guardian, witnesses and the Islamic marriage contract, just do not do the recording at the office of the Religious Affairs (KUA) as an official from the Ministry of Religion for those who perform marriages according to Islam and at the offices of those who hold civil marriage according to religious beliefs other than Islam. Without a recording then indirectly the government has not recognized the official bond, so there are matters relating to the rights of children and a wife who cann’t be met. Therefore, this study wanted to examine how Islam views nikah siri after seen the negative consequences thereof.